2010
DOI: 10.1140/epja/i2010-11017-x
|View full text |Cite
|
Sign up to set email alerts
|

On parity-violating three-nucleon interactions and the predictive power of few-nucleon EFT at very low energies

Abstract: We address the typical strengths of hadronic parity-violating three-nucleon interactions in "pion-less" Effective Field Theory in the nucleon-deuteron (iso-doublet) system. By analysing the superficial degree of divergence of loop diagrams, we conclude that no such interactions are needed at leading order, O(ǫQ −1 ). The only two distinct parity-violating three-nucleon structures with one derivative mix 2 S 1 2 and 2 P 1 2 waves with iso-spin transitions ∆I = 0 or 1. Due to their structure, they cannot absorb … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 31 publications
6
45
1
Order By: Relevance
“…The analysis of Ref. [29] showed that no such enhancement of a PV three-nucleon contact term occurs at LO and NLO in nucleon-deuteron scattering. This means that up to an accuracy of approximately 10%, it is possible to analyze few-nucleon observables in terms of PV two-nucleon interactions.…”
Section: Pos(cd15)043mentioning
confidence: 99%
“…The analysis of Ref. [29] showed that no such enhancement of a PV three-nucleon contact term occurs at LO and NLO in nucleon-deuteron scattering. This means that up to an accuracy of approximately 10%, it is possible to analyze few-nucleon observables in terms of PV two-nucleon interactions.…”
Section: Pos(cd15)043mentioning
confidence: 99%
“…In Ref. [19], it was shown that such an enhancement does not occur for PV three-nucleon interactions and that they do not contribute at LO and NLO. Therefore, up to an accuracy of roughly 10%, few-nucleon observables can be described by PV twonucleon interactions alone.…”
Section: Three-nucleon Systemsmentioning
confidence: 99%
“…[26] (and refer the reader there for all details), but add to the potential the N 2 LO correction in Eq. (28). Since this term involves no new LECs, the extraction of the LECs works in exactly the same way.…”
Section: A Refit Of H π Using Part Of the N 2 Lo Potentialmentioning
confidence: 99%